Effect of a traction-assist winch on wheel slippage and machine induced soil disturbance in flat terrain. (26th July 2021) - Schönauer, Marian; Holzfeind, Thomas; Hoffmann, Stephan; Holzleitner, Franz; Hinte, Bastian; Jaeger, Dirk
ABSTRACT: Recently, forest operations are facing unfavorable climatic conditions more frequently. In Central Europe, machine trafficability and induced soil disturbances are negatively affected by periods of high precipitation and less intensive frost during ground-based harvesting operations. Winch-assist technology is assumed to reduce soil disturbance by forest machines in steep terrain. Still, the potential positive effects of winches to assist traction of forest machines in flat terrain have rarely been surveyed. In this study, a field trial was conducted in flat terrain (slope < 5%). There, a forwarder with an integrated traction-assist was monitored during six consecutive machine passes on a permanent machine operating trail. The first section of the machine operating trail was passed without traction-assist, the remaining section with traction-assist, resulting in two treatment groups. To assess soil impacts, three test plots were positioned per treatment group. Within these plots, pre- and post-operational soil bulk density, soil displacement and rutting were determined. Additionally, wheel slippage and cable tensile force were examined, using incremental rotary encoders and a flexible tensile force measurement kit, respectively. It was observed, that wheel slippage responded inversely with tensile force. Traction-assist technology reduced wheel slippage from 5.3 ± 11.9% to 0.37 ± 10.19% along the section of the machine operating trail, as compared to results from the unassisted section. Although wheel slippage was significantly reduced, no mitigating effect by the usage of traction-assist technology on soil disturbance could be observed, probably due to the low volumetric water content of 27%.